Chromosome analysis of Quercus castaneifolia - Najafi, S.; Tuncturk, R.; Tuncturk, M.; Seyyedi, N. (International Journal of Agricultural Technology, 2021)
The results showed that all studied cells of each population, the basic chromosome number was x=12 and all of them were diploid. Karyotype analysis of each population was conducted separately and several indices (TL: Total Length, LA: Long Arm, SA: Short Arm, CI: Centromer Index, AR: Arm Ratio, R- value, DRL%: Difference of Relative Length and TF%: Total Form) were determined. Karyotype formula was 12m in all studied populations. The length of chromosomes in all populations was estimated as 1.55-2.68 micrometers. The longest chromosome was observed in chromosome number 1 from population 4 (Gorghan) which was 2.68 micrometers and the shortest one was related to the chromosome number 12 from population 5 (Zanoos) which was 1.55 micrometers. Considering of chromosomal classification, all the studied populations were placed in class 1A of Stebbins which showed that there is a symmetry in the studied karyotypes. The other estimated indices also showed that in chromosomes are relatively symmetric in all populations that indicated this species is primitive and undeveloped